Estimating The Inflation-Growth Nexus-A Smooth Transition Model - Espinoza, Raphael (IMF Working Papers; Working Paper, 2010)
Motivated by the global inflation episode of 2007-08 and concern that high levels of inflation could undermine growth, this paper uses a panel of 165 countries and data for 1960-2007 to revisit the nexus between inflation and growth. We use a smooth transition model to investigate the speed at which inflation beyond a threshold becomes harmful to growth, an important consideration in the policy response to rising inflation as the world economy recovers. We estimate that for all country groups (except for advanced countries) inflation above a threshold of about 10 percent quickly becomes harmful to growth, suggesting the need for a prompt policy response to inflation at or above the relevant threshold. For the advanced economies, the threshold is much lower. For oil exporting countries, the estimates are less robust, possibly reflecting heterogeneity among oil producers, but the effect of higher inflation for oil producers is found to be stronger.